Impaired processing of emotion in music, faces and voices supports a generalized emotional decoding deficit in alcoholism. (20th August 2012) - Kornreich, Charles; Brevers, Damien; Canivet, Delphine; Ermer, Elsa; Naranjo, Cecilia; Constant, Eric; Verbanck, Paul; Campanella, Salvatore; Noël, Xavier
Abstract Aim To test the generalized emotional decoding impairment hypothesis in alcoholism. Design Cross‐sectional behavioural study comparing emotion recognition conveyed by faces, voices and musical excerpts. Setting Alcohol detoxification unit of Brugmann University Hospital. Participants Twenty‐five recently detoxified alcohol‐dependent patients were compared to 25 normal controls matched for sex, age and educational level. Measurements From faces, voices and musical excerpts, participants were instructed to rate the intensity of several emotions on a scale from 0 for 'absent' to 9 for 'highly present'. Depression, anxiety and sustained/selective attention capacities were controlled for. Findings Alcohol‐dependent patients were less accurate than controls in identifying the target emotion in faces (P < 0.001), voices (P < 0.001) and musical excerpts (P < 0.001). Conclusions Alcohol‐dependent patients who are completing detoxification are impaired in recognizing emotions conveyed by faces, voices and music; these results suggest a generalized emotional decoding impairment. Hypothetically, deficits in the fronto‐parietal mirror neurone system could link all these disturbances together.